Decline in Chinese lake phosphorus concentration accompanied by shift in sources since 2006 - Tong, Yindong; Zhang, Wei; Wang, Xuejun; Couture, Raoul-Marie; Larssen, Thorjørn; Zhao, Yue; Li, Jing; Liang, Huijiao; Liu, Xueyan; Bu, Xiaoge; He, Wei; Zhang, Qianggong; et al. (Nature geoscience, 2017)
Domestic wastewater and agricultural activities are important sources of nutrient pollutants such as phosphorus and nitrogen. Upon reaching freshwater, these nutrients can lead to extensive growth of harmful algae, which results in eutrophication. Many Chinese lakes are subject to such eutrophication, especially in highly polluted areas, and as such, understanding nutrient fluxes to these lakes offers insights into the varying processes governing pollutant fluxes as well as lake water quality. Here we analyse water quality data, recorded between 2006 and 2014 in 862 freshwater lakes in four geographical regions of China, to assess the input of phosphorus from human activity. We find that improvements in sanitation of both rural and urban domestic wastewater have resulted in large-scale declines in lake phosphorus concentrations in the most populated parts of China. In more sparsely populated regions, diffuse sources such as aquaculture and livestock farming offset this decline. Anthropogenic deforestation and soil erosion may also offset decreases in point sources of pollution. In the light of these regional differences, we suggest that a spatially flexible set of policies for water quality control would be beneficial for the future health of Chinese lakes. Many lakes in China are subject to eutrophication. Water quality analyses on 862 Chinese lakes reveal that better sanitation has reduced phosphorus inputs in the most populated areas, but aquaculture and livestock offset improvements elsewhere.